2016
DOI: 10.3389/fpsyg.2016.01015
|View full text |Cite
|
Sign up to set email alerts
|

The Relation between Effortful Control and Language Competence—A Small But Mighty Difference between First and Second Language Learners

Abstract: The present longitudinal study evaluates the effect of effortful control (EC) as a core dimension of temperament on early language competence. We assume that first and second language competence is influenced by EC, and that immigrant children with low EC are thus at risk of an unfavorable language development. The sample consisted of n = 351 dual language learners (DLLs) with an immigrant background and n = 78 monolingual children. Language competence was measured with a standardized language test at age 4.9 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 39 publications
0
5
0
Order By: Relevance
“…By definition, dual language learners are children who are regularly exposed to, understand, and/or can produce one (or more) language(s) at a basic level of functional proficiency or use ( Castro, 2014 ). Many dual language learning children in Switzerland and Germany do not experience their first regular contact with the societal language until preschool or kindergarten ( Autorengruppe Bildungsberichterstattung, 2020 ;Keller et al, 2016 ). One aim of these childcare settings is to provide children with a favourable start at school, which includes the acquisition of sufficient societal language skills ( Klein & Becker, 2017 ).…”
Section: Dual Language Learnersmentioning
confidence: 99%
“…By definition, dual language learners are children who are regularly exposed to, understand, and/or can produce one (or more) language(s) at a basic level of functional proficiency or use ( Castro, 2014 ). Many dual language learning children in Switzerland and Germany do not experience their first regular contact with the societal language until preschool or kindergarten ( Autorengruppe Bildungsberichterstattung, 2020 ;Keller et al, 2016 ). One aim of these childcare settings is to provide children with a favourable start at school, which includes the acquisition of sufficient societal language skills ( Klein & Becker, 2017 ).…”
Section: Dual Language Learnersmentioning
confidence: 99%
“…Similarly, Ishikawa-Omori et al (2022) did not find a predictive link between Effortful Control at 18 months and language development at 40 months. Keller et al (2016) only demonstrated a significant relationship in the second language competence of dual language learners in childhood. The lack of predictive power of Effortful Control preceding the age of language assessment in the regression models and the separately observed concurrent correlation are in line with these results.…”
Section: Discussionmentioning
confidence: 87%
“…The link between effortful control and language development remains unclear, despite some studies ( Salley and Dixon, 2007 ; Keller et al, 2016 ) suggesting a positive relationship that could potentially be attributed to varying attentional capacities, which are thought to support language acquisition ( Snijders et al, 2020 ). Effortful Control, as measured by Rothbart’s temperament questionnaires, is related to the functioning of the executive network ( Posner et al, 2016 ).…”
Section: Discussionmentioning
confidence: 99%
“…Across both ages, children’s effortful control and surgency were positively correlated, and negative affect negatively correlated with vocabulary and MLU. As prior work suggests, a child’s ability to focus/attend (effortful control; Keller, Troesch, Loher, & Grob, 2016) and socialize (surgency; DeThorne, Deater‐Deckard, Mahurin‐Smith, Coletto, & Petrill, 2011) are critical for language, whereas fussiness (negative affect) detracts from learning (Dixon & Salley, 2007; Garello et al., 2012; Usai, Garello, & Viterbori, et al., 2009). Contrary to expectations, shyness was not correlated with vocabulary.…”
Section: Discussionmentioning
confidence: 99%